Rapid microwave synthesis of fluorescent hydrophobic carbon dots - Mitra, Shouvik; Chandra, Sourov; Kundu, Tanay; Banerjee, Rahul; Pramanik, Panchanan; Goswami, Arunava (RSC Advances, 2012)
Fluorescent hydrophobic carbon dots (HCDs) have been fabricated from a poloxamer by a simple microwave assisted process within a few minutes for the first time. Small and distinct spherical HCDs emitted bright blue and green fluorescent light depending upon the excitation wavelength and were dispersed easily in a wide variety of organic solvents. HCDs exhibited excellent water resistant behavior with a contact angle of similar to 122 degrees enforcing good hydrophobic character which will be quite useful in potential surface applications.